GAMBARAN TINGKAT PENGETAHUAN REMAJA SMA TENTANG BAHAYA BULLYING - Noviana, Ema; Pranata, Lilik; Fari, Aniska Indah (Publikasi Penelitian Terapan dan Kebijakan, 2020)
Bullying is a deliberate behavior of the perpetrator to hurt the victim. It is not negligent yet truly intentional behavior. The effects of bullying include appetite loss, low enthusiasm in doing preferred activities, learning achievement decline, depression, and impaired self-control that potentially lead to suicide. Purpose: This study aims to describe the senior high schools students’ knowledge level on the dangers of bullying. Methods: This study used a quantitative approach with a descriptive research design. A sample of 98 respondents was selected using total sampling. Results: The results of the study involving 98 respondents showed that there were 96 (98%) students in middle adolescence aged 15-17 years old. More female respondents participated with a total of 57 respondents (58.2%). More respondents who had sufficient knowledge level of bullying with a total of 48 respondents (49%). Suggestion: It is expected that this study increases the insight and knowledge about the dangers of bullying that frequently happen among the senior high school students. The future researchers are recommended to conduct further analysis and correlation between the adolescent knowledge level and academic performance variable.